Study on Storage Rate and Economical Performance of Ice-storage Air-conditioning System - 杜雁霞; 贾代勇; 耿世彬 (Zhileng xuebao)
Based on the traditional methods of economic analysis for cool storage system, the paper takes into account the initial investment, operation cost of additional equipment and the management cost of system, analyses the impacts of storage rate upon economical performance combined with a typical project example. The curves of storage rate versus initial investment, annual operation cost and payback years are obtained.